Pro Dynamic .NET 4.0 Applications Data-Driven Programming for the .NET Framework - Ganz, Carl.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
As a developer you are likely painfully aware that not all features of an application can be anticipated when the software ships. In order to cope with these eventualities and save yourself time (and perhaps money), it makes sense to write your applications in such a way that end users can be made as independent of the developers as possible. Giving your users the power to make changes to the way the application operates once it has shipped gives them more control over the way the application works, while reducing the frequency with which you need to redistribute application files, creating a win-win situation. Pro Dynamic .NET 4.0 Applications explains how to give users the power to create additional data-entry fields, validation logic, and new reports without assistance from the application developer. You will learn how to do this for both desktop (C# and WPF) and web (ASP) applications.
Introducing Data-Driven Programming -- Reflection -- Runtime Code Compilation -- Dynamic WinForms -- Dynamic ASP.NET -- Dynamic WPF -- Reporting -- Database Design.
Keywords: Computer science; Computer Science; Programming Techniques